2001
DOI: 10.1088/0953-2048/14/9/328
|View full text |Cite
|
Sign up to set email alerts
|

Growth-related profiles of remanent flux in bulk melt-textured YBaCuO crystal magnetized by pulsed fields

Abstract: We have studied the remanent magnetic flux distribution in bulk melttextured YBa 2 Cu 3 O 7−δ (YBCO) crystals after their magnetization in quasi-static and pulsed magnetic fields up to 6 T . It has been shown that, provided that the magnetic pulse is sharp enough and its amplitude much exceeds the twice penetration magnetic field, the pulse magnetization technique becomes extremely sensitive to the sample inhomogeneities. Using this method with appropriate parameters of the magnetic pulse, we have particularly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…[4,5], and post-annealed in oxygen atmosphere. The YBCO crystal appeared a large single grain (please, note nearly regular tetragonal shape of isolines on the remanent flux map, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5], and post-annealed in oxygen atmosphere. The YBCO crystal appeared a large single grain (please, note nearly regular tetragonal shape of isolines on the remanent flux map, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…That is why Dewhurst et al observed a certain degradation of the crystal microstructure in the radial direction (from the crystal center towards the edges) and, because of a short coherence length ξ (e.g., ξ c ≈ 0.3 nm and ξ ab ≈ 2 nm in the YBa 2 Cu 3 O 7−δ (YBCO) material), that of superconducting properties [3]. Apart from the radial inhomogeneities the lateral ones were also recently revealed [4]. In particular, the lateral distribution of a flux trapped by the YBCO crystal after its magnetization by short magnetic pulses, was demonstrated to ensue from its growth in five growth sectors (GS), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(9)-(11) and the Green function (6) into Eq. (5). The expressions are given for a general case of having different field ramp rates R A and R D on the ascending and descending branch, respectively.…”
Section: Appendix Amentioning
confidence: 99%
“…Whereas the PFM activation method is the most convenient from practical point of view, even higher fields have been trapped by quasi-static field ramping. 2,3,4,5 This shortcoming of PFM cannot be overcome by simply increasing the maximal applied field B M . In fact, it is found experimentally that the trapped flux reaches maximum at some optimal value B M = B opt , and decreases for larger B M .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation